PENGARUH BENTUK DAUN LONTAR TERHADAP INTENSITAS BUNYI ALAT MUSIK SASANDO - Afrianus Gelu; Sulhadi Sulhadi; Teguh Darsono; Kristianus Liwa (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Sasando is one of traditional music instrument from Rote Ndao Regency, East Nusa Tenggara. Sasando classified as musical instruments chordophone because played by way of plucked. One of the compilers of the construction of the Sasando is a leaf of the lontar (siwalan). This study aims to determine the influence of changes in the shape of leaves lontar (siwalan) horizontally to the intensity of the sound produced. The horizontal width of the lontar leaves was varied by 30 cm, 35 cm, 40 cm, 45 cm, 50 cm, and 55 cm. The intensity of the sound that is produced is measured using a Sound Level Meter (SLM). Based on the research results obtained show that there is change the value of the sound intensity if the diameter of the horizontal palm leaf changed its size. The value of the sound intensity the average Sasando change varies from 9,68 x 10-7 W/m2 up to a 2,85 x 10-5 W/m2. The value of the intensity of the sound of most high is at a diameter of 40 cm while the value of the sound intensity that most low located on a diameter of 30 cm. Keywords: Sasando, lontar, sound intensity